HUMAN RESOURCE MANAGEMENT PRACTICES AND CHALLENGES IN RURAL MSMES: A CASE STUDY IN SAKTI VILLAGE, SOUTH BOLAANG MONGONDOW - Rendi Setiyawan Pou; Ikram Muhammad; Moh Ikbal Kadir (Journal of Economic, Business, and Administration (JEBA), 2026)
This study aims to analyze the implementation of Human Resource Management (HRM) practices in developing the potential of Micro, Small, and Medium Enterprises (MSMEs) in Sakti Village, Posigadan District, South Bolaang Mongondow Regency, North Sulawesi Province. The study employed a qualitative descriptive approach using in-depth interviews, observations, and documentation techniques. Informants consisted of village government representatives and MSME owners selected through purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings reveal that HRM practices among MSMEs in Sakti Village remain predominantly informal and unstructured. Human resource planning is conducted based on immediate operational needs without systematic workforce forecasting. Recruitment and selection rely heavily on family networks and personal trust rather than competency-based criteria. Human resource development is limited to informal learning through direct guidance and work experience, with minimal access to formal training programs. Compensation and incentives are adjusted according to business financial capacity and are not supported by structured reward systems. Performance evaluation is conducted subjectively through direct observation without standardized indicators or formal assessment mechanisms. These findings indicate that HRM functions have not yet been implemented strategically, which may limit productivity, workforce development, and business competitiveness. The study concludes that strengthening HRM practices through more systematic planning, competency-based recruitment, continuous employee development, structured compensation systems, and objective performance evaluation is essential to support the sustainability and growth of MSMEs in Sakti Village.